2018
DOI: 10.1016/j.jsat.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in tobacco use prevalence, behaviors, and cessation services by race/ethnicity: A survey of persons in addiction treatment

Abstract: Some findings reflected broader population patterns (e.g., tobacco use behaviors, other tobacco product use), while others did not (e.g., no difference in tobacco use prevalence by race/ethnicity). The reasons for greater receipt of cessation services among African Americans are unclear. Findings indicate the need for continued engagement of African Americans and Hispanics in cessation services while in addiction treatment, and for addressing heavier tobacco use and lack of interest in cessation during treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…Notably, our observation that the proportion of dual users was higher than that of polytobacco users has not been reported in previous research in SUD populations. In addition, consistent with previous studies among SUD samples, 12,13 we found that e-cigarettes were the This study extends the existing literature by indicating factors associated with dual-and polytobacco use among people in SUD treatment. Current tobacco users who had ever used e-cigarettes for quitting smoking were more likely to be both dual-and polytobacco users.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, our observation that the proportion of dual users was higher than that of polytobacco users has not been reported in previous research in SUD populations. In addition, consistent with previous studies among SUD samples, 12,13 we found that e-cigarettes were the This study extends the existing literature by indicating factors associated with dual-and polytobacco use among people in SUD treatment. Current tobacco users who had ever used e-cigarettes for quitting smoking were more likely to be both dual-and polytobacco users.…”
Section: Discussionsupporting
confidence: 91%
“…In furtherance of the burgeoning base of literature in support of anhedonia as a novel component of the tobacco withdrawal syndrome (Cook et al, 2015(Cook et al, , 2017Hughes et al, 2017;Piper et al, 2017), our findings suggest that deprivation-induced anhedonia may be implicated in the smoking patterns of AA smokers, who are considerably more likely to relapse following a quit attempt (Kulak et al, 2016;Pagano et al, 2018;Weinberger et al, 2019). Given the motivational salience that deprivation-induced generalized consummatory may have on smoking lapse and relapse among AA smokers, the current findings provide empirical justification for incorporating anhedonia into standard tobacco withdrawal assessment and targeting anhedonia in smoking cessation behavioral interventions used with AA smokers.…”
Section: Discussionmentioning
confidence: 69%
“…Keywords: anhedonia, consummatory anhedonia, anticipatory anhedonia, tobacco withdrawal, African-American smokers Supplemental materials: https://doi.org/10.1037/pha0000474.supp African-American (AA) smokers bear a disproportionate brunt of the public health burden of smoking (Henley et al, 2016;Simmons et al, 2016). Relative to white smokers, AA smokers are considerably more likely to relapse following quit attempts despite being more likely to initiate them (Kulak et al, 2016;Pagano et al, 2018;Weinberger et al, 2019). A major barrier to tobacco cessation both within the general smoking population and among AA smokers, the tobacco withdrawal syndrome is a set of unpleasant symptoms that emerge shortly after the discontinuation of sustained tobacco use (American Psychiatric Association, 2013;Hooper et al, 2017;Weinberger et al, 2017).…”
mentioning
confidence: 99%
“…An additional study found less e-cigarette use in Black and Hispanic relative to White tobacco users. 116 The role of health care stakeholders (eg, medical schools, hospitals, and health insurance providers) in vaping cessation is not to be overlooked. Medical schools should develop curriculum on the risks of vaping, both long and short term.…”
Section: Regulatory Measuresmentioning
confidence: 99%